Corporate Social Responsibility: An Uneasy Merger of Sustainability and Development. (17th April 2013) - Luke, Timothy W.; Springett, Delyse
ABSTRACT This study reevaluates the origins and operations of corporate social responsibility (CSR) programs since the 1980s and 1990s in the USA. Such enterprises mobilize sustainable development rhetoric as part of stylized political agendas for community outreach, social impact, cultural sensitivity and environmental justice campaigns endorsed by big business. These campaigns react to political pressures exerted by local, national or global anti‐corporate movements, and sustainable development has become one moderately successful negotiated settlement in this battle between the private sector and civil society. Nonetheless, a brittle quality in weak interpretations of sustainable development remains engrained in many CSR programs as standard operating procedures. These profit‐driven agendas push for 'development' over 'sustainability', lowering the bar for what sustainability should, or does, mean for businesses as they struggle to be more responsible ethical actors in society. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.